Rosacea is More than Just a Red Face: Microbotox's Role in Minimizing Enlarged Facial Pores for a Rosacea Patient - Jaya Nagara, Adianto; Wydya Yenny, Satya; Fadhilla, Yola; Norawati, Lilik; Arimuko, Abraham (Journal La Medihealtico, 2024)
Enlarged facial pores are a cosmetic concern and a prominent feature of skin aging that impacts patient quality of life. Microbotox has emerged in multiple studies as a solution for reducing pore size and improving skin texture. A case of 29 years old female with papulopustular rosacea and enlarged skin pores was reported. From the patient's anamnesis, it was found that the patient has been complaining of a reddish patch with pimples on the nose and both cheeks for the past 4 years. The patient has also had enlarged pores on both cheeks for the past 3 years. On dermatologic state there were erythematous macule, erythematous papules and enlarged pores on both of the cheek. Global Flushing Severity Score (GFSS) was 3, Investigator’s Global Assessment (IGA) of Rosacea Severity for papules and pustules is grade 2 and erythema grade 2. Visual Assessment for Pore was 6. Patient received a single session of microbotox. Dermoscopy examination showed linear vessels (telangiectasia), a pustule, and also follicles filled with sebum. Follow up of the patient was done for 6 weeks. Patients reported a decrease in issues such as flushing, papules, pustules, and erythema. A noticeable improvement in pore size was also observed. This action can be repeated every 3 months to maintain clinical improvement and good skin texture. Botulinum toxin exhibits a satisfying level of efficacy and safety in rosacea treatment. A single microbotox session proves to be a safe and effective approach for reducing facial pore size, along with notable improvements in skin texture.